Visualization and Legalization of K.H. Ahmad Dahlan's Hisab Method in Tafsir al-Azhar by Hamka (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2021)
This study is intended to examine the effect of the hisab-rukyat methodology of K.H. Ahmad Dahlan on Hamka's interpretation, explanation, and illustration in his work, Tafsir Al-Azhar. These two figures are linked by the Muhammadiyah organization where K.H. Ahmad Dahlan was the founder and central figure of his time, while Hamka was a cadre who later became a prominent cleric, even an icon of Muhammadiyah. This research is a library research with a narrative-analytical model. Data were collected from primary sources in the form of Tafsir Al-Azhar by Hamka. This study shows that Hamka is quite accommodating to the reckoning and rukyat methods, even though Muhammadiyah is organizationally inclined to reckoning. However, Hamka put emphasis on prioritizing reckoning because it is in line with advances in science and technology. Hamka shows an objective-reformist typology of thought, namely a combination of classical and modern thought that is directed at reform. This study is expected to contribute to the enrichment of perspectives on the reckoning method that has developed in Indonesia, so that the method of calculating time or the Hijri calendar is not stuck in a new state, and even triggers tensions between Muslims with different organizational affiliations.